Pathological Studies on Mortality of Dairy Calves and the Associated Risk Factors - Malik, Sunil; N Prabhu, Shyama; Pratap Singh, Ajay; Kumar Gangwar, Neeraj; Arun, Ambika; Singh Arya, Rahul; Deepak Singh, Desh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This study analyzed mortality causes in 27 calves (0-6 months). Most deaths occurred in neonates (0-3 months), primarily from pneumonia  (various forms) and enteritis. Bacterial isolates included E. coli, Salmonella (enteritis), Staphylococcus, and Klebsiella (pneumonia). Parasites  (Coccidia, Toxocara, Theileria, etc.) were also identified. Pneumonia and enteritis were identified as the predominant pathological  conditions. Pneumonia was manifested in various forms, including bronchopneumonia, interstitial pneumonia, and granulomatous  pneumonia. Various types of enteritis seen were catarrhal, necro-hemorrhagic, hemorrhagic, necrotic, and proliferative. Mortality  correlated with delayed colostrum intake (>2 h), poor ventilation, and inadequate deworming, but not with birth weight, gender, or  herd size. While bacterial and parasitic causes were confirmed, viral agents were not investigated. Larger studies including viral screening  are needed for comprehensive understanding.
Keywords: Calf mortality; Enteritis; Pneumonia; Risk factors